Od historii idei do historii literatury. Kilka uwag i propozycji metodologicznych - Goliński, Janusz K. (Litteraria Copernicana, 2008)
A choice of literary evidences in studies on old literature must show not only their historical and theoretical, aesthetic and philological separateness but also it should be opened to searching for man (rooted in the world and culture), it should provoke questions about his nature and fortune. Finally topics, threads, motives and pictures that are reached including and considering lingual-stylistic, compositive and genealogical phenomena are material of „read” texts. The subject of studies – „necessarily bordering” and „polyphonic” – should become what appears from texts: an image of man and his experience among the world. Wandering across areas of old literature must reveal „subjects” and „pictures” that require „reading”, exploring meanings and understanding; here „thematic criticism” is necessary – focused on „contents of a literary work” subordinated to some thematic units, therefore naturally aiding research on the border of history of literature and history of thinking comprehended as an internal experience. It is interesting to note that the thematic units are just characterized by special intensity of the media, beside relations within literature they determine relations between literature and „life”, between literature and a sphere of philosophical thought, between literature and other fields of art.